Ekspresi Diri pada Supporter Punk Football di Dunia Sepak Bola - febri nur faturohman; Dedeh Fardiah (UNISBA Press, 2023)
Abstract. Football has become a sport that is in great demand by the wider community. In addition to being interested in playing soccer, many of the players are connoisseurs or commonly referred to as football Supporters. Over time, football in Indonesia itself experienced many changes and problems in it. And in this day and age, football teams and their Supporters often experience problems with each other. Riverside Forest was born out of all the unrest in Indonesian football. Carrying Punk Football, Riverside Forest is a football klub that is funded and built by its own Supporters. In addition, Supporters in every support team always convey a kampanye as a form of self- expression to the world of football today. Based on that, the author is interested in researching the Self-Expression of Riverside Forest Supporters in Delivering kampanyes in the World of Football. Using qualitative methods and case study approaches. Data collection techniques used are interviews, observation and document analysis. Abstrak. Sepak bola sudah menjadi olahraga yang banyak diminati oleh masyarakat luas. Selain diminati untuk dimainkan sepak bolapun banyak peminatnya sebagai penikmat atau biasa disebut dengan Supporter sepak bola. Seiring berjalannya waktu sepak bola di Indonesia sendiri banyak mengalami perubahan dan problematika di dalamnya. Dan di zaman sekarang ini tim sepak bola dengan Supporternyapun sering mengalami suatu permasalahan satu sama lain. Riverside Forest lahir dari segala keresahan yang ada di sepak bola Indonesia. Mengusung Punk Football, Riverside Forest menjadi klub sepak bola yang didanai dan dibangun oleh Supporternya sendiri. Selain itu, Supporter dalam setiap mendukung tim selalu menyampaikan kampanye sebagai bentuk ekspresidiri terhadap dunia persepakbolaan sekarang ini. Berlandasan dari itulah penulis tertarik meneliti mengenai Ekspresi Diri Supporter Riverside Forest dalam menyampaikan kampanye di Dunia Sepak Bola. Menggunakan metode kualitatif dan pendekatan studi kasus. Teknik pengumpulan data yang digunakan yaitu wawancara, observasi dan analisis dokumen.